Physical Facilities for Learning Outcomes: A Study of Sindh Madressatul Islam University - Badee U Zaman Kehar; Safdar Shah (International Journal of Education Sciences, 2025)
The physical facilities are the significant features for ideal learning outcomes. The physical environment greatly influences students' psychological, sociological, and intellectual growth, and we cannot ignore them in the postmodern world. For this purpose, the research was undertaken on physical facilities and their impacts on students’ learning outcomes at Sindh Madressatul Islam University, Karachi, Sindh, Pakistan. The study employed quantitative methodology, gathering information via surveys. There were 100 people in the sample. There were five departments with regular students enrolled. The results were obtained by applying a percentage formula to the data. The results showed that learning outcomes are greatly impacted by physical amenities. The vast majority of respondents concurred that a cozy and healthful environment is necessary for efficient learning, underscoring the need of well-maintained facilities in learning environments. The study emphasizes how spending on physical infrastructure can improve academic achievement, motivation, and student participation. Prioritizing excellent learning environments allows educational institutions to establish supportive places that foster student development, so reinforcing the crucial connection between the caliber of physical resources and academic achievement. In the end, this research encourages institutions to acknowledge the wider effects of physical surroundings on student accomplishment and overall development and promotes intentional upgrades in educational infrastructure to promote improved learning outcomes.
Keywords: Academic Achievement; Students; educational infrastructure; learning outcome; physical facilities